Chapter I santuari gesuati - BIGGI, Laura (Fragmentaria. Studi di storia culturale e antropologia religiosa, 2020)
The historical studies on shrines paid little attention to Yesuati's shrines and this paper starts analyzing the causes of this phenomenon. The essay presents four shrines managed by the povari di Cristo, highlighting both the similarities and the differences in their management of the shrines of central Italy, between XVth and XVIth centuries. From the comparison between these case studies emerges a substantially positive experience of the Yesuati inside Marian shrines - despite the obstacle represented by their impossibility to exercise the function of priests -, both for practical reasons (give assistance to the poor people ) and for spiritual reasons (the povari's ecclesiology and mariology).